Overview on the intercalation of gold into graphite. (April 2019) - Fauchard, Mélissa; Cahen, Sébastien; Lagrange, Philippe; Berger, Pascal; Hérold, Claire
Abstract: The intercalation of gold into graphite has been achieved thanks to a solid-liquid method using potassium metal-based molten alloys. Numerous syntheses have been performed varying the reactive alloy composition, the reaction temperature and the reaction time. The optimization of these parameters allowed to synthesize three novel ternary graphite intercalation compounds (GIC) containing poly-layered intercalated sheets, called alpha, beta and gamma. Thanks to a specific X-Ray diffraction study, the c -axis stacking sequence of the three compounds was determined. The α-GIC, which is a metastable compound, contains mixed potassium and gold two-layered intercalated sheets. The β-GIC and γ-GIC contain very thick well ordered three-layered and five-layered sheets respectively. The very high repeat distances of the latter compounds are clearly explained by the amount of intercalated metals, precisely determined using nuclear microprobe analyses. Graphical abstract: Image 10204706